Acute toxicity of deltamethrin for freshwater mussel, Unio elongatulus eucirrus bourguignat - Koprucu, K.; Seker, E. (Springer, 2008)
In this study, the acute toxicity of deltamethrin, contaminating aquatic ecosystems as a pollutant, on freshwater mussel, Unio elongatulus eucirrus, was examined. Deltamethrin was applied at concentrations of 1, 2, 3, 4, 5, 6, 7, 8, 16 and 32 mg L-1. The 1, 24, 48, 72 and 96 h LC50 values of deltamethrin for freshwater mussels were determined as 10.07, 8.99, 8.09, 7.30 and 6.60 mg L-1, respectively. There were significant differences in LC10-90 values obtained for different times of exposure. The results show that deltamethrin is moderately toxic for freshwater mussel and it should be used with caution in agriculture to protect natural waters from contamination.
Keywords: freshwater mussel; Unio elongatulus eucirrus; deltamethrin; acute toxicity